Faktor-Faktor Tugas Ketua Tim terhadap Kepuasan Kerja Perawat Pelaksana - Asep Paturohman; Tri Kurniati; Luknis Sabri (Jurnal Keperawatan Silampari, 2021)
This study aims to determine the dominant factor of Katim's task in the management process of directing motivation, communication, cooperation, conflict handling, and supervision, with the job satisfaction of the nurse executing. The method used in this research is quantitative research with the cross-sectional approach. The results showed a relationship between Katim duties in the management process of directing motivation p-value 0.04, communication p-value 0.001, cooperation p-value 0.034, and no relationship between Katim duties in the management process executing conflict handling p-value 0.41 and supervision p-value 1. The most dominant factor that increases the nurse's job satisfaction in charge is the task of Katim in the management process of directing conflict handling OR 20.097. In conclusion, the excellent direction will increase the job satisfaction of nurses. Keywords: Job Satisfaction, Team Leader, Implementing Nurse